Pharmacological and Non-pharmacological Means for Prevention of Fractures among Elderly - Fares, Auda (Int J Prev Med, 2018)
Fractures are major cause of morbidity, mortality, and healthcare and social services expenditure in elderly. Fractures often have multifactorial etiologies and the condition emerges due to the interaction between the different predisposing and precipitating factors. One of the most common causes leading to fractures after minimal trauma in older people is osteoporosis. The objective of this article is to describe the clinical concept and summarize the evidence and to explain the future directions for research, focusing on specific issues related to prevent fracture in the elderly. This study reviewed the scientific literature addressing strategies for primary and secondaryprevention of fractures among elderly in the context of pharmacological and non-pharmacological means. A growing body of scientific evidence supports the use of both non-pharmacological and pharmacological interventions for the prevention of fracture. Research on these interventions has yielded positive outcomes in fracture rates. The bisphosphonates and vitamin D and calcium suppliments are the preferred therapy for prevention of osteoporotic fractures. Weight-bearing exercise and reducing home hazards have beneficial effects in reducing the incidence of falls and consequently reduce fractures. Prevention of fractures in elderly consists of therapy and prevention of osteoporosis, fall prevention, and using injury-site protection by high-risk elderly patients. Special consideration needs to be taken to reduce home hazard, and falls prevention education can be recommended to the elderly with history of fall or mobility limitations. Future research to prevent fractures in elderly population should not only concentrate on improving bone density and strength but also need to be focused on falls reduction strategies.